SERVANT LEADERSHIP AND EMPLOYEE WELLBEING: A MODERATED MEDIATION FRAMEWORK - Muhammad Ashfaq; Dr. Maria Saleem; Atta Muhammad; Dr. Faisal Mahmood; Shahbaz Haneef (Policy Research Journal, 2025)
Attaining optimal levels of job satisfaction is imperative for stability, competitiveness, and sustainability of the banking industry. This underscores the critical role of employee well-being in stimulating organizational resilience and prolonged success within the sector. The banking industry is identified by its notably demanding framework and employee-intensive practices, presenting considerable challenges in sustaining job satisfaction and promoting employee well-being. Servant leadership has a crucial role in improving job satisfaction and employee well-being. The objective of this research framework to foster the job satisfaction and investigated the relationship between the servant leadership and employee wellbeing by mediation of job satisfaction under the boundary condition of job resource and job demand underpinning the social exchange theory. Present study implemented a quantitative research design and chased the post positivist paradigm Supported by research question and the development to theory is deductive as this study intends to investigated the causal relationship among the research variable. This is multi-source mono method quantitative research by applied time lagged framework to attain primary data by following a survey strategy through multiple Self- conducted questionaries. The selected population of this study is commercial bank are regulated by state bank of Pakistan in Punjab province. The sample for this research encompasses 150 commercial banks and 750 employees, nominated to share a comprehensive representation of the target population. This research study managed the systematic framework of analysis by utilizing SPSS and smart PLS software. The findings indicated that job satisfaction established a mediated positive relationship between servant leadership and employee wellbeing. The result investigated that servant leadership Can serve the aspiration as a result-oriented leadership strategies to Elevate job satisfaction and employee well.